2012
DOI: 10.3325/cmj.2012.53.244
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement in the war in Croatia 1991-1995 and suicidality in Croatian male adolescents

Abstract: AimTo investigate the association between parental war involvement and different indicators of psychosocial distress in a community sample of early adolescents ten years after the war in Croatia 1991-1995.MethodsA total of 695 adolescents were screened with a self-report questionnaire assessing parental war involvement, sociodemographic characteristics, and alcohol and drug consumption. Personality traits were assessed with the Junior Eysenck Personality Questionnaire; depressive symptoms with the Children’s D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Suicidality is reported in the literature as being a non-specific marker for a broad range of psychosocial distresses such as political unrest and poor life quality [23]. These have been previously shown to negatively impact mental health at the individual level, potentially to the extent of self-harm [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Suicidality is reported in the literature as being a non-specific marker for a broad range of psychosocial distresses such as political unrest and poor life quality [23]. These have been previously shown to negatively impact mental health at the individual level, potentially to the extent of self-harm [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found higher depression among those youths who blamed others for their parent’s suicide (36) and those with high exposure to rocket attacks and low social support (37). Negative psychosocial outcomes in children were also associated to parental involvement in the Croatian war 1991-1995, especially among boys (14). In our study, more war traumatized group had a significantly positive correlation with the desire to be in the company of attractive people, which is in agreement with a higher result for socialization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of children and adolescents from Bosnia and Herzegovina (7-13), Croatia (14,15), Cambodia (16), and Israel and Palestine (17) showed that growing up and living in war conditions increased anxiety, depression, and PTSD symptoms, but also most of children, in traumatic situations, enhanced the ways of active coping with intellectual and emotional focusing (18). …”
mentioning
confidence: 99%
“…The included publications are predominantly American (n = 13, see Tables 2 and 3a). Two are Croatian (Franić et al, 2012;Maršanić et al, 2014), and one publication is Dutch (Andres & Moelker, 2011). The countries of deployment represented in the publications are mainly Iraq and/or Afghanistan.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Thirteen publications are based on samples regarding children living with veterans deployed to Iraq, of which two are based on a Gulf War sample (Kelley, 1994a(Kelley, , 1994b. Seven publications include children living with veterans deployed to Afghanistan (Andres & Moelker, 2011;Lester et al, 2010Lester et al, , 2012Lester et al, , 2013Letamendi, 2012;Reed, Bell, & Edwards, 2011;Wilson et al, 2011), and four publications report on samples comprising children living with veterans from the Balkan conflict (Andres & Moelker, 2011;Franić et al, 2012;Maršanić et al, 2014;Wilson et al, 2011). Several of the publications are, however, based on samples that include children of veterans deployed to different countries: Iraq and Afghanistan: five (Lester et al, 2010(Lester et al, , 2012(Lester et al, , 2013Letamendi, 2012;Reed, Bell, & Edwards, 2011), Bosnia and Afghanistan: one (Andres & Moelker, 2011), and multiple countries including Iraq, Afghanistan, and Bosnia: one (Wilson et al, 2011); see Table 3a.…”
Section: Sample Characteristicsmentioning
confidence: 99%